Vitamin D: Possible Therapeutic Roles in Hepatocellular Carcinoma - Adelani, Isaacson B.; Rotimi, Oluwakemi A.; Maduagwu, Emmanuel N.; Rotimi, Solomon O. (Frontiers in Oncology, 2021)
Hepatocellular carcinoma (HCC) is a unique type of liver cancer instigated by underlying liver diseases. Pre-clinical evidence suggests that HCC progression, like other cancers, could be aided by vitamin D deficiency. Vitamin D is a lipid-soluble hormone usually obtained through sunlight. Vitamin D elucidates its biological responses by binding the vitamin D receptor; thus, promoting skeletal mineralization, and maintain calcium homeostasis. Other reported Vitamin D functions include specific roles in proliferation, angiogenesis, apoptosis, inflammation, and cell differentiation. This review highlighted studies on vitamin D’s functional roles in HCC and discussed the specific therapeutic targets from various in vivo, in vitro and clinical studies over the years. Furthermore, it described recent advancements in vitamin D’s anticancer effects and its metabolizing enzymes’ roles in HCC development. In summary, the review elucidated specific vitamin D-associated target genes that play critical functions in the inhibition of tumorigenesis through inflammation, oxidative stress, invasion, and apoptosis in HCC progression.